From idea to realization. Rhetorical analysis of the TV documentary by Michał Fajbusiewicz and Waldemar Piasecki entitled “My Mission” - Grzegorzewski, Krzysztof (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The chapter is an analysis of the TV documentary “My Mission” directed by Michał Fajbusiewicz and Waldemar Piasecki. The author decided to analyze the film using the theory of classical rhetoric, focusing the reader's attention on the composition. The text is divided into three parts: invention, disposition and elocution. Invention means: collecting journalistic material for publication through: journalistic interview (its broad and narrow definition), research of sources in the form of books, press texts, historical documents, social life documents and cultural texts as well. Disposition means: organizing the material according to the principles of journalistic art and in accordance with the artistic vision of the authors of the film (especially Fajbusiewicz). Elocution is expressed in the linguistic, visual and audial aspect of the film, reduced to typical rhetorical traces and figures.